High crystalline, porous polyamide 6 by anionic polymerization. (28th February 2018) - Rahman, Md Arifur; Renna, Lawrence A.; Venkataraman, D.; Desbois, Philippe; Lesser, Alan J.
Abstract: Polyamide 6 (PA6), also known as Nylon 6 is a widely used industrial polymer. The structural properties of PA6 play an important role in its potential commercial applications. We report that the anionic polymerization of ε-caprolactam in the presence of liquid additives such as o-Xylene, m-Xylene, p-Xylene and toluene at a critical concentration led to the formation of high crystalline, porous polyamide 6 (aPA6). Porous aPA6 samples possess hierarchical spherulitic morphology where 10 μm size spherulitic granules are interconnected by submicron size fibrillated domains. The size and shape of spherulitic domains change with the type of liquid additives used during the synthesis of porous aPA6. The presence of liquid additives influences the kinetics of the exothermal processes during polymerization, which ultimately leads to a solid-liquid phase separation prior to the formation of porous networks of spherulites. Such process also leads to thickening of lamella and formation of second order crystals that contributed to highest crystallinity in porous aPA6 ever reported. Differential scanning calorimetric along with wide-angle X-ray scattering study reveal ∼60% crystallinity in all porous aPA6, which is about 60% increase in comparison with the neat aPA6 (∼40%). Higher crystallinity in porous aPA6 also exhibited 50% reduction in moisture uptake in comparison with the neat aPA6. Graphical abstract: Highlights: Synthesized porous polyamide 6 by modified anionic polymerization of ε-caprolactam. Hierarchically porous morphology possess ∼10 µm size spherulites and submicron size fibrillated domains. Presence of axialitic crystals contributed to high crystallinity (60%). High crystallinity contributed to 50% reduction in moisture absorption in polyamide 6. The open, interconnected porosity also contributed to selective filtration property.